1970
DOI: 10.1063/1.1674102
|View full text |Cite
|
Sign up to set email alerts
|

Shock Wave Compression of Three Polynuclear Aromatic Compounds

Abstract: Polycrystalline samples of anthracene, phenanthrene, and pyrene have been stressed with shock waves to pressures of 550 kbar. States in the stressed samples were determined by measuring shock wave velocities in the samples and in an 1100 aluminum base plate used as a standard. An abrupt increase in the compressibility was noted for each material: it occurred at 176 kbar for anthracene, 201 kbar for phenanthrene, and 234 kbar for pyrene. This increase is believed to be associated with an intermolecular coupling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 8 publications
(4 reference statements)
0
20
0
Order By: Relevance
“…6 As pressure increases, benzene has been found to decompose at 13 GPa along its Hugoniot. [7][8][9][10][11] At high static and dynamic temperatures and pressures, benzene mainly converts into defective carbon nanoparticles and H 2 , with the possible products of small concentrations of polycyclic aromatic hydrocarbons, such as alkanes. 12,13 Such reactions have also been found to be similar to the detonation of explosive materials.…”
Section: The Equation Of State and Nonmetal-metal Transition Of Benzementioning
confidence: 99%
See 1 more Smart Citation
“…6 As pressure increases, benzene has been found to decompose at 13 GPa along its Hugoniot. [7][8][9][10][11] At high static and dynamic temperatures and pressures, benzene mainly converts into defective carbon nanoparticles and H 2 , with the possible products of small concentrations of polycyclic aromatic hydrocarbons, such as alkanes. 12,13 Such reactions have also been found to be similar to the detonation of explosive materials.…”
Section: The Equation Of State and Nonmetal-metal Transition Of Benzementioning
confidence: 99%
“…Researches on benzene properties under shock conditions start from the plate impact experiments [6]. As pressure increases, benzene has been found to decompose at 13 GPa along its Hugoniot [7,8,9,10,11]. At high static and dynamic temperatures and pressures, benzene mainly converts into defective carbon nanoparticles and H 2 , with the possible products of small concentrations of polycyclic aromatic hydrocarbons, such as alkanes [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…5,7 However, the peak pertaining to dimeric anthracene extends over several tens of amu, demonstrating that subsequent reactions of the dimers could be occurring. Warnes 5 suggested that one such reaction might be dehydrogenation.…”
Section: Dehydrogenation Reactionsmentioning
confidence: 99%
“…Similar to that of benzene, the Hugoniot of liquid benzene has a discontinuity in its slope ͑i.e., a cusp, at 17.6 GPa͒. 5 Warnes suggested, based on mass spectrometry data, that one chemical product of shocked anthracene could be bianthracenyl ͑C 28 H 18 ͒. In 1994, Engelke and Blais 7 confirmed the production of chemically bound dimer above pressures of 18.4 GPa, corresponding roughly to the cusp in the shock Hugoniot of anthracene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation